Art and illusion : a study in the psychology of pictorial representation - Gombrich, E. H. (Ernst Hans), 1909-2001. (Princeton : Princeton University Press, 2000)
"Considered a great classic by all who seek a meeting ground between science and the humanities. Art and Illusion examines the history and psychology of pictorial representation in light of present-day theories of visual perception information and learning. Searching for a rational explanation of the changing styles of art, Gombrich reexamines many ideas on the imitation of nature and the function of tradition.
In testing his arguments he ranges over the history of art, noticing particularly the accomplishments of the ancient Greeks, and the visual discoveries of such masters as Leonardo da Vinci and Rembrandt, as well as the impressionists and the cubists. Gombrich's main concern is less with the artists than with ourselves, the beholders."--BOOK JACKET.
Introduction: Psychology and the Riddle of Style -- Pt. 1. The Limits of Likeness -- I. From Light into Paint -- II. Truth and the Stereotype -- Pt. 2. Function and Form -- III. Pygmalion's Power -- IV. Reflections of the Greek Revolution -- V. Formula and Experience -- Pt. 3. The Beholder's Share -- VI. The Image in the Clouds -- VII. Conditions of Illusion -- VIII. Ambiguities of the Third Dimension -- Pt. 4. Invention and Discovery -- IX. The Analysis of Vision in Art -- X. The Experiment of Caricature -- XI. From Representation to Expression.
Includes bibliographical references (p. [399]-441) and index.
Keywords: Art -- Psychology; Art -- Psychologie